Functional characterization and directed evolution of Cicer arietinum glutathione transferases for enhanced hydroperoxidase activity and ligandin function - Kontouri, Anni; Georgakis, Nikolaos; Papageorgiou, Anastassios C.; Labrou, Nikolaos Ε. (Pergamon Press, 2026)
Tau class glutathione transferases (GSTUs) play essential roles in plant defense by facilitating the nucleophilic attack of glutathione (GSH) to a wide range of electrophilic xenobiotics. In addition to their conjugating activity, these enzymes possess hydroperoxidase function, enabling the detoxification of harmful organic hydroperoxides into less reactive alcohols. In this study, we identified three closely related GST isoenzymes (96–98 % sequence identity) from Cicer arietinum (CaGSTUs) through computational homology screening. Full-length cDNAs encoding these GSTs were cloned, recombinantly produced in E. coli, and purified for functional characterization. Enzyme kinetics were evaluated using model substrates, cumene hydroperoxide (CuOOH) and 1-chloro-2,4-dinitrobenzene (CDNB), revealing that CaGSTU1-1 displayed superior hydroperoxidase activity and thermal stability. Based on these properties, CaGSTU1-1 was selected as the parental scaffold for directed evolution via DNA shuffling, using the homologous Glycine max isoenzyme GmGSTU4-4. Screening of the generated chimeric library resulted in the identification of a new variant, CaGmGSTU, which demonstrated a fourfold enhancement in catalytic turnover and efficiency toward both substrates. Additionally, CaGmGSTU exhibited altered ligand-binding characteristics, including increased affinity for selected pesticides. Structural modeling and viscosity-dependence kinetics indicated that these enhancements were primarily driven by changes in enzyme flexibility. Given the widespread toxicity of hydroperoxides and related pollutants, CaGmGSTU represents a promising tool for detoxification applications in environmental and agricultural biotechnology.